Caregiver mental health and HIV-infected child wellness: perspectives from Ugandan caregivers. Issue 6 (3rd June 2017) - Murray, S. M.; Familiar, I.; Nakasujja, N.; Winch, P. J.; Gallo, J. J.; Opoka, R.; Caesar, J. O.; Boivin, M. J.; Bass, J. K.
ABSTRACT: Prior studies indicate a substantial link between maternal depression and early child health but give limited consideration to the direction of this relationship or the context in which it occurs. We sought to create a contextually informed conceptual framework of this relationship through semi-structured interviews with women that had lived experience of caring for an HIV-infected child while coping with depression and anxiety symptoms. Caregivers explained their role in raising healthy children as complex and complicated by poverty, stigma, and isolation. Caregivers discussed the effects of their own mental health on child well-being as primarily emotional and behavioral, and explained how looking after a child could bring distress, particularly when unable to provide desired care for sick children. Our findings suggest the need for investigation of the reciprocal effects of child sickness on caregiver wellness and for integrated programs that holistically address the needs of HIV-affected families.